Cage‐Opened C60 Isomers with Different Reactivities. Issue 3 (21st January 2022) - Zhang, Sheng; Hashikawa, Yoshifumi; Murata, Yasujiro
Abstract: We synthesized two cage‐opened C60 isomers with different arrangement of an imine moiety on their orifices and investigated reactivities of them toward nucleophiles. Both isomers underwent the enlargement of the opening by the reaction with N ‐methylmorpholine N ‐oxide in comparable yields while the reaction with MeOH caused an orifice contraction via a transannular cyclization resulting in obviously different yields. The products in the latter reaction have a new hexagonal or heptagonal ring on their skeletons. The observed difference in reactivity could be explained by the greater thermodynamic stabilization in the hexagon‐containing isomer compared with the other. Abstract : Two open‐cage C60 isomers having an opposite arrangement of a C=N bond showed similar reactivities toward N ‐methylmorpholine N ‐oxide. Contrastingly, in the reaction with methanol, the L isomer underwent an efficient transannular cyclization while the R isomer gave an unstable product in low yields.